An analytical study of rainfall pattern over Chennai - NATARAJAN, S.; RAMAKRISHNAN, B.; RAMANATHAN, RM. A. N. (MAUSAM, 2004)
The spells of daily rainfall received at Nungambakkam and Meenambakkam observatories located in Chennai for ten year period have been analysed. The study reveals that the spells have three distinct patterns with February and March having negligible spells while April to September being 15 to 20 percent and from October to January having very high values. The spells that occur during southwest monsoon season are having high consistency of occurrence during evening, night and early morning where as the spells during northeast monsoon are equally spread during the whole day. Frequency of one or two spells per day is more during the months January to September. There is significant increase in the value of two spells and more during October to December. In the months of June to September more than 65 percent of the rainy days, the duration of rainfall in a day is less than 2 hours while October to December the value of percentage is below fifty. The number of spells of rainfall with amount of rainfall less than two millimeters is about 55 percent throughout the year. The intensity of spells of rain of less than 7 millimeters per hour ranges from 60 to 70 percent for all the months except for the month of March.